(untitled) (KULT_online, 2015)
Tomasz Zarycki’s interdisciplinary study investigates constructions of "Eastness" across Central and Eastern Europe, focusing on Poland and its elites. The country is framed as both an object and producer of orientalizing discourses. The book, incorporating multiple disciplinary approaches, including sociology, politics, geography and history, becomes a work of cultural studies as it applies postcolonial theory to this "semi-peripheral" region. What emerges is a wide-ranging investigation of the effects of "ideologies" of Eastness, with findings spanning macro-level economic consequences through to the micro-level transformation of local identity constructions.